Statistical behavior of shear layers of reactive oxygen/kerosene spray. (October 2019) - Choi, Songyi; Ahn, Junsun; Koo, Jaye
Abstract: Reactive gaseous oxygen/kerosene spray was visualized by a shadowgraph imaging technique in a lab-scale rocket engine combustor. Dynamic behaviors of inner and outer shear layer were observed morphologically and analyzed quantitatively by image processing. Correlation methods were used to statistically analyze dynamic behaviors of each shear layer and interaction between two shear layers. Relationship between shear layer dynamics and combustion flow-field was investigated by analyzing periodicity of jet-core length, lump-detachment, and luminous flame intensity. The results of correlation and frequency analysis show that dominant frequency of behaviors and interaction of shear layers is 270 Hz and the degree of correlation becomes stronger along the flow direction. The dominant frequency of core length variation and luminous flame formation is around 270 Hz and, which is the same as that of behaviors and interaction of shear layers. This proposes that the surface behaviors and interaction of the inner and outer jets in the upstream affect the downstream combustion flow-field. Highlights: Behavior of two shear layers in reactive spray was detected from shadowgraph images. Correlation methods were used to characterize behavior of shear layers and interaction between them. Behavior and interaction of shear layers correlate to inner jet breakup and formation of luminous flame.